Total serum calcium and corrected calcium as a predictor of severity in acute pancreatitis - T., Kemparaj; K. N., Narasimhamurthy; Muralidhar, Archit (International Surgery Journal, 2018)
Background: Acute pancreatitis is an acute inflammatory process of the pancreas. The Ranson and the modified Glasgow scores require 48 hours of data collection to asses’ severity. Hypocalcaemia is one of the components of Ranson’s scoring system done to assess the severity of pancreatitis. Albumin-corrected calcium (ACC) has also been associated with severity, but no study has evaluated it as a prognostic severity factor within the first 24 h of the patient’s hospital admission. This study tries to evaluate total calcium and albumin corrected calcium as prognostic severity markers in acute pancreatitis within first 24 hour of admission. Methods: This prospective study was conducted in Bowring and Lady Curzon hospital, a tertiary care centre from June 2016 to May 2018. Inclusion criteria included all patients above 18 years of age, who presented within 72 hours of onset of epigastric pain. The clinical and demographic data with respect to gender, age, previous history of pancreatitis, total calcium taken 24 h after admission. In order to evaluate total calcium and albumin corrected calcium as prognostic factors of severity, the lowest total calcium values were collected within the first 24 h of hospital admission. These values were then corrected according to the serum albumin level. Results: A total of ninety-four patients were included in the study. There was no significant difference in the age of patients in each severity grade (p value: 0.242). No difference was observed in gender distribution of three groups. (P >0.05). As compared to total calcium, mean values of albumin corrected calcium were 8.03, 7.18 and 6.28 for mild, moderate and severe acute pancreatitis respectively, which were also significant at 0.05. Conclusions: Total calcium and albumin-corrected calcium obtained within the first 24 hours of hospital admission are useful predictors of severity in acute pancreatitis.